2010
DOI: 10.1128/jcm.00137-10
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Single Nucleotide Polymorphism Typing Method for Identification of Bacillus anthracis Species and Strains among B. cereus Group Species

Abstract: As an issue of biosecurity, species-specific genetic markers have been well characterized. However, Bacillus anthracis strain-specific information is currently not sufficient for traceability to identify the origin of the strain. By using genome-wide screening using short read mapping, we identified strainspecific single nucleotide polymorphisms (SNPs) among B. anthracis strains including Japanese isolates, and we further developed a simplified 80-tag SNP typing method for the primary investigation of traceabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The ability to cluster related isolates and differentiate unrelated isolates is crucial for understanding the population biology of S. suis. Whole-genome comparative analysis and collection of high-confidence global SNPs provide ideal typing targets for investigating the population structure of bacterial species (24)(25)(26). The reliability of phylogenetic inference based on MLST is adversely affected by the frequency of recombinations that obscure phylogenetic signals, as S. suis is a weakly clonal species.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to cluster related isolates and differentiate unrelated isolates is crucial for understanding the population biology of S. suis. Whole-genome comparative analysis and collection of high-confidence global SNPs provide ideal typing targets for investigating the population structure of bacterial species (24)(25)(26). The reliability of phylogenetic inference based on MLST is adversely affected by the frequency of recombinations that obscure phylogenetic signals, as S. suis is a weakly clonal species.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies (20,22,53), it has been shown that the NAP7-NAP8 strain type is highly divergent from other strain types and that the C. difficile core genome may be composed of only ϳ1,000 genes (20,22,53,58). To date, MPS and comparative genome analyses of C. difficile have not been applied to the search for additional DNA-based diagnostic targets, as has been done for other human pathogens (6,14,15,28).…”
mentioning
confidence: 99%
“…The advent of next-generation sequencing technologies and comparative genome analyses offers a powerful approach for identifying rare polymorphisms for the unbiased typing of highly clonal pathogens. Since 2007, and the identification by Van Ert et al of 13 "canonical" SNPs representing key phylogenetic positions along the B. anthracis phylogenetic SNP tree, a growing number of diagnostic SNPs has been discovered and used to survey B. anthracis diversity in nature [11] [24] [30]- [32]. In this study, a same but large-scale approach, comparing 161 B. anthracis genomes of diverse origins, were conducted to discover novel informative SNPs that can further discriminate within lineages or groups of strains.…”
Section: Discussionmentioning
confidence: 99%